General approach for anisotropic magnetoresistance calculations used for revealing the role of cobalt nanowire’s geometrical details - Ferreira Velo, Murilo; Puydinger dos Santos, Marcos Vinicius; Malvezzi Cecchi, Breno; Roberto Pirota, Kleber (Journal of magnetism and magnetic materials, 2021)
•Anisotropic magnetoresistance (AMR) measurements of magnetic nanowire grown by focused-electron-beam-induced deposition.•Micromagnetic simulations combined with classical electromagnetism reproduce the main features of the experimental AMR of the magnetic nanowire.•The voltage terminals induce growth of domain walls (DWs) around them during the magnetization reversal of the nanostructure.•The propagation features of the DWs are the main responsible for the AMR signal behaviour. The electrical resistivity modulation by the application of external magnetic fields, known as magnetoresistance effect (MR), is a widely studied subject driven by both technological applications and fundamental challenges, although being difficult to make numerical predictions from first analytical principles. In this work, we present a MR simulator protocol that combines micromagnetics with classical electrodynamics and works well for room temperature anisotropic magnetoresistance (AMR) for a large magnetic field variation range. As a proof of concept, we applied it to simulate the AMR of a previously reported Co-C composite nanostructure defined by a central nanostripe as the current line with transversal voltage contacts. In addition to the macroscopic measurable quantities like average magnetization and MR signal, the method returns the microscopic spatial magnetization distribution and gives insights about the magnetization reversal mechanism. For example, for this particular case, the magnetic domain walls are predominantly nucleated near the magnetic voltage terminals and their propagation features are the main responsible for the MR observed behavior. Other elements can be easily incorporated to the protocol in order to simulate materials with additional complexities such as crystalline grains or magnetocrystalline anisotropy.